2010
DOI: 10.1007/s11604-010-0464-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance-guided vacuum-assisted breast biopsy: results in 100 Japanese women

Abstract: The high rate of DCIS might be a unique feature among Japanese women. However, MRI-guided VAB is necessary for MRI-only visible suspicious lesions in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 21 publications
4
20
2
Order By: Relevance
“…The rate of diagnosis of malignancy using ultrasound-guided VAB was significantly lower because of the lack of distinction between diagnostic and therapeutic ultrasound-guided VABs and the generally lower pretest likelihood of malignancy of the BI-RADS 3 lesions usually selected for ultrasound-guided VAB. The rate of malignancy detection achieved using MRI-guided VAB corresponds with those (22–33 %) previously reported [4, 22, 24, 28, 3032]. …”
Section: Discussionsupporting
confidence: 87%
“…The rate of diagnosis of malignancy using ultrasound-guided VAB was significantly lower because of the lack of distinction between diagnostic and therapeutic ultrasound-guided VABs and the generally lower pretest likelihood of malignancy of the BI-RADS 3 lesions usually selected for ultrasound-guided VAB. The rate of malignancy detection achieved using MRI-guided VAB corresponds with those (22–33 %) previously reported [4, 22, 24, 28, 3032]. …”
Section: Discussionsupporting
confidence: 87%
“…Our initial experience showed that the success rate of MRI-guided VABB was 86.7% (13/15). This rate is slightly lower than the 96 to 100% technical success rates reported in prior studies of MRI-guided VABB [6-9,11,12,14]. The median procedural time in our study was 55.7 minutes.…”
Section: Discussioncontrasting
confidence: 67%
“…If a lesion is deemed to be not accessible to MR-VAB, MR-guided needle localization followed by surgery can be performed. Our results are in agreement with previous findings in literature 1519…”
Section: Discussionsupporting
confidence: 94%